Studi Komparatif Aspek Literasi Keuangan Perempuan Bali dan Perempuan Non-Bali terhadap Keberlangsungan Usaha di Kecamatan Buleleng - Switariyani, Made Dewi; Kusuma Dewi, Luh Gede; Vijaya, Diota Prameswari (Vokasi : Jurnal Riset Akuntansi, 2025)
Balinese women had limited time to manage their businesses due to social and cultural obligations, while non-Balinese women were more flexible but had not fully optimized their financial literacy. This study aimed to analyze the financial literacy aspects of Balinese and non-Balinese women in relation to business sustainability in Buleleng District. A qualitative method was used, with data collected through observations, interviews, and documentation from women entrepreneurs. The findings show that Balinese women tend to be more cautious in managing finances and rarely use formal financial services. In contrast, non-Balinese women are more active in financial planning and tend to use business credit as additional capital. However, both groups still do not separate personal and business finances, leading to difficulties in financial evaluation and accessing formal capital. Therefore, context-based financial literacy education is essential to improve financial management and support long-term business sustainability.